Development of NARA biodegradable journaling books as a circular economy-based solution for sustainable lifestyle transformation and social empowerment - Ahmad Arro’uf Sulfuadi; Ferdian Anugrah Pratama; Muhammad Imam Baihaqi (EcoProfit: Sustainable and Environment Business, 2026)
Background: Sustainability challenges have prompted higher education institutions to reconsider intensive paper consumption that contributes to waste and carbon emissions. Prior studies show that student behavior can be influenced through sustainable product design, yet affordable and functional eco-friendly academic products remain limited. Meanwhile, corn husk waste is underutilized despite its potential as a biodegradable material. This study aims to develop and evaluate a biodegradable journaling product made from recycled paper and corn husks as a circular economy–based solution supporting sustainable lifestyles and social empowerment. Methods: This study employed an applied product development approach integrated with the voice of customer (VoC) method. Product development included material selection, prototype design, and the incorporation of circular economy principles. User data were collected through an online structured questionnaire distributed to university students in the Special Region of Yogyakarta, Indonesia. Quantitative data were analyzed using descriptive statistics, while qualitative responses were thematically analyzed to capture user perceptions regarding functionality, sustainability attributes, and social value. Findings: The VoC analysis shows that users prioritize motivational and environmental insights (47.4%), habit tracking features (41.2%), and digital synchronization through reminders or Quick Response (QR)-based systems (36.8%). These findings indicate that sustainable journaling products are more effective when cognitive motivation, behavioral monitoring, and digital convenience are integrated. The results support behavioral design theory, which suggests that sustainable behavior adoption is strengthened through the combination of inspiration, accountability, and usability. Conclusion: This study demonstrates that agricultural waste and literature-based content can be transformed into a user-centered and sustainable academic product through structured product development and VoC integration. Novelty/Originality of this article: This research uniquely integrates biodegradable material innovation, behavioral journaling design, and user-centered product development within a circular economy framework while incorporating social empowerment at the farmer level.